“TARMOQ TEXNOLOGIYALARI” FANINI O‘QITISHDA AMALIYOTGA YO‘NALTIRILGAN YONDASHUVDAN FOYDALANISH - Alaminov, M.X. (SCIENCE and SOCIETY, 2024)
The research of the topic allowed the author to identify the main stages of the formation of knowledge, skills and practical skills within the framework of lectures and laboratory sessions: theoretical preparation, modeling of computer networks using modern information technologies, and practical implementation of networks to solve problems. increase Technologies for teaching the course using a practice-oriented approach have been developed.
Keywords: network technology; modeling; emulation